2018
DOI: 10.1007/s10661-018-6833-x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment concerning trace metals and ecological risks at Guanabara Bay, RJ, Brazil

Abstract: Three-stage sequential extraction BCR was applied to surface sediments from the west part of Guanabara Bay to assess the mobility of Zn, Cu, Pb, Ni, Cr, and Mn. Results were satisfactory for the analysis of certificate standard material (BCR 701), with recoveries between 71 (Cu) and 123% (Cr). Evaluation of organic matter composition classified the area as eutrophic (CHO:PRT > 1), with aged organic detritus at some stations. Zn exhibited by far the greatest bioavailability, with 43.49% of its concentrations as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…(2014) highlighted that several trace elements, such as Pb, Ni, Cu, Cd, and Zn, were found at high levels in the Canal do Cunha basin. These trace elements were observed in the surface sediments from other parts of Guanabara Bay (Aguiar et al ., 2018; Baptista Neto et al ., 2000) and showed a strong correlation with some dinocysts (Freitas, Aguiar, and Baptista Neto, 2021). The majority of samples analysed in the present study showed extremely high values when compared to background values for Guanabara Bay (Baptista Neto et al ., 2000; Monteiro et al ., 2012).…”
Section: Discussionmentioning
confidence: 72%
“…(2014) highlighted that several trace elements, such as Pb, Ni, Cu, Cd, and Zn, were found at high levels in the Canal do Cunha basin. These trace elements were observed in the surface sediments from other parts of Guanabara Bay (Aguiar et al ., 2018; Baptista Neto et al ., 2000) and showed a strong correlation with some dinocysts (Freitas, Aguiar, and Baptista Neto, 2021). The majority of samples analysed in the present study showed extremely high values when compared to background values for Guanabara Bay (Baptista Neto et al ., 2000; Monteiro et al ., 2012).…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, the assessment of actual pollution levels and the identification of appropriate management policies may be difficult (Masiol et al 2014). Many studies dealt with assessment of metals pollution in coastal areas or river catchments worldwide, focusing especially on trace elements in sediments in Europe (Alharbi and El-Sorogy 2017) (Charizopoulos et al 2016;Couto et al 2018;Nagy et al 2016;Rodriguez et al 2018) and worldwide (Batbayar et al 2017;De Carvalho Aguiar et al 2018;Vystavna et al 2018).…”
Section: Introductionmentioning
confidence: 99%